ATF3 Suppresses Growth and Metastasis of Clear Cell Renal Cell Carcinoma by Deactivating EGFR/AKT/GSK3β/β-Catenin Signaling Pathway - Gao, Shenglin; Gao, Lei; Wang, Simin; Shi, Xiaokai; Yue, Chuang; Wei, Shuzhang; Zuo, Li; Zhang, Lifeng; Qin, Xihu (Frontiers in Cell and Developmental Biology, 2021)
Background Clear cell renal cell carcinoma (ccRCC) is one of the most common malignant cancers in East Asia, with high incidence and mortality. Accumulating evidence has shown that ATF3 is associated with tumor progression. Methods Using qPCR, the expression of ATF3 was detected in 93 patients with ccRCC, including 24 paired normal and tumor tissues, which were used to further compare ATF3 expression through western blotting and immunohistochemistry. Lentivirus was used for the overexpression or knockdown of ATF3, and the consequent alteration in function was analyzed through CCK8 assay, colony formation assay, wound healing assay, invasion assay, and flow cytometry. The potential mechanism affected by ATF3 was analyzed through gene set enrichment analysis (GSEA) and verified using western blotting, invasion assay, or immunofluorescence staining. Furthermore, a xenograft mouse model was used to assess the function of ATF3 in vivo. Results ATF3 expression was significantly decreased in ccRCC compared to that in adjacent normal tissues. Through gain- and loss-of-function experiments performed in an in vitro assay, we found that ATF3 could regulate ccRCC cell proliferation, cycle progression, migration, and invasion. In the in vivo study, the xenograft mouse model revealed that ATF3 overexpression can inhibit the growth of ccRCC. Moreover, the mechanism analysis showed that suppression of ATF3 could lead to an increase the expression of β-catenin and promote β-catenin transfer to the nucleus, and might be affected by EGFR/AKT/GSK3β signaling. Conclusion ATF3 could be utilized as an independent protective factor to inhibit the progression of ccRCC. Potential treatment strategies for ccRCC include targeting the ATF3/EGFR/AKT/GSK3β/β−catenin signaling pathway.